Computing H/D-Exchange rates of single residues from data of proteolytic fragments - Althaus Ernst; Canzar Stefan; Ehrler Carsten; Emmett Mark R; Karrenbauer Andreas; Marshall Alan G; Meyer-Bäse Anke; Tipton Jeremiah D; Zhang Hui-Min (BMC Bioinformatics, 2010)
Abstract Background Protein conformation and protein/protein interaction can be elucidated by solution-phase Hydrogen/Deuterium exchange (sHDX) coupled to high-resolution mass analysis of the digested protein or protein complex. In sHDX experiments mutant proteins are compared to wild-type proteins or a ligand is added to the protein and compared to the wild-type protein (or mutant). The number of deuteriums incorporated into the polypeptides generated from the protease digest of the protein is related to the solvent accessibility of amide protons within the original protein construct. Results In this work, sHDX data was collected on a 14.5 T FT-ICR MS. An algorithm was developed based on combinatorial optimization that predicts deuterium exchange with high spatial resolution based on the sHDX data of overlapping proteolytic fragments. Often the algorithm assigns deuterium exchange with single residue resolution. Conclusions With our new method it is possible to automatically determine deuterium exchange with higher spatial resolution than the level of digested fragments.